Strategi Pengembanga Manajemen Diklat untuk Meningkatakan Kualitas Sumber Daya Manusia : Indonesia - Nihayatus Yudha; M. Yudha Hutama; Susilo Surahman (Universitas Persatuan Guru 1945 NTT, 2026)
In today's global world, developing human resources through education and training is very important for a company's success. This research looks at the challenges organizations face in a competitive environment, where the quality of human resources often decides the outcome. The goal of this study is to create good strategies for managing training programs to improve the skills and performance of employees. The study uses a review of three main journals, looking at both the ideas and real-world practices of training management. The findings show that using digital tools, focusing on employee skills, and regularly checking progress can make training more effective. The study concludes that these strategies are important for long-term improvements in employee quality, and suggests that companies should use mixed methods in managing their training programs.